Analisis Pengaruh Keberadaan Mall Ciputra Seraya Terhadap Kinerja Jalan Riau-Pekanbaru - Zulfahmi Zulfahmi; Elianora Elianora; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The high growth of the number of vehicles will cause a smooth flow of traffic, and an increase in the number of population is also greatly effect the congestion that occurs. The number of vehicles and activities in Pekanbaru city causes social and economic problems that very depend on road transportation. This problem arises because of an imbalance between increased vehicle owners and the growth of road infrastructure. Traffic congestion is one problem that has long been faced in the Pekanbaru region. As seen on the roads of Riau as one of examples of standards that is experiencing congestion. This research aims to know the influence of the existence of the Mall Ciputra Seraya on performance of Riau Street caused by activities such as vehicles exit sign in the mall, pedestrians, and vehicles parked or stopped at the roadside. Traffic Data, Side Barriers Data and Traveling Time Data collected through surveys during rush-hour on Saturday. Analysis of road performance based on the Indonesian Road Capacity Manual (MKJI) method 1997 to get the value of the capacity, the Side Barriers, the degree of Saturation of the road and velocity. As for the capacity, the Riau road at 3046 smp/hour and the highest peak current occurred on Saturday at 16.30-17.30 amounting to 2333 pcu/hour, Side Barriers 513 with class categories High Side friction (H), Degree of Saturation (DS) is 0.77, Vehicle speed 26.9 km/hour and included on the level of service is D i.e. approaching unstable flow (low speed).Keywords: Traffic performance, Congestion, Side Barriers, Capacity, Degree of Saturation, Velocity